Anti-LGBT and Anti-immigrant Structural Stigma: An Intersectional Analysis of Sexual Minority Men's HIV Risk When Migrating to or Within Europe. (1st December 2017) - Pachankis, John E.; Hatzenbuehler, Mark L.; Berg, Rigmor C.; Fernández-Dávila, Percy; Mirandola, Massimo; Marcus, Ulrich; Weatherburn, Peter; Schmidt, Axel J.
Abstract : Objective: Gay, bisexual, and other men who have sex with men (MSM) might be particularly likely to migrate to experience freedoms unavailable in their home countries. Structural stigma (eg, laws and policies promoting the unequal treatment of oppressed populations) in MSM migrants' sending and receiving countries represent potential barriers to HIV prevention among this intersectional population. This study represents the first investigation of structural determinants of HIV risk in a large, geographically diverse sample of MSM migrants. Design: The 2010 European MSM Internet Survey (n = 23, 371 migrants) was administered across 38 European countries. Methods: Structural stigma was assessed using (1) national laws and policies promoting unequal treatment of sexual minorities across 181 countries worldwide and (2) national attitudes against immigrants in the 38 receiving countries. We also assessed linguistic status, time since migrating, and 5 HIV-prevention outcomes. Results: Structural stigma toward sexual minorities (in sending and receiving countries) and toward immigrants (in receiving countries) was associated with a lack of HIV-prevention knowledge, service coverage, and precautionary behaviors among MSM migrants. Linguistic status and time since migrating moderated some associations between structural stigma and lack of HIV prevention. Conclusions: Structural stigma toward MSM and immigrants represents a modifiable structural determinant of the global HIV epidemic.